Have policy responses in Nigeria resulted in improvements in infant and young child feeding practices in Nigeria?. Issue 1 (December 2016) - Ogbo, Felix; Page, Andrew; Idoko, John; Claudio, Fernanda; Agho, Kingsley
Abstract Background Nigeria initiated a range of programs and policies (from 1992 to 2005) to improve infant and young child feeding (IYCF) practices. However, the prevalence of children fed in accordance with IYCF recommendations in Nigeria remains low. This paper presents time trends in IYCF practices in Nigeria for the period (1999–2013), and considers trends in the context of key national policy responses and initiatives. Methods Prevalence and percentage change (including 95% confidence intervals) of IYCF indicators were investigated over the period 1999–2013 based on a total of 88, 152 maternal responses from the Nigeria Demographic and Health Surveys, (n = 8, 199 in 1999;n = 7, 620 in 2003;n = 33, 385 in 2008 andn = 38, 948 in 2013). Results Early or timely initiation of breastfeeding decreased significantly by 4.3% (95% Confidence Interval [CI]: −8.1, −0.5;p = 0.0280 for the period (1999–2013); while exclusive breastfeeding remained unchanged 1.6% (95% CI: −2.7, 5.9;p = 0.478). From 2003 to 2013, minimum meal frequency increased significantly by 13.8% (95% CI: 9.9, 17.8;p < 0.001), but minimum dietary diversity and minimum acceptable decreased significantly by 9.7% (95% CI: −9.2, −6.3;p < 0.001) and 3.5% (95% CI: −5.7, −1.3;p = 0.002), respectively. Predominant breastfeeding increased significantly by 13.1% (p < 0.001), and children ever breastfed declined by 16.4% (p < 0.001) over time. Conclusion Despite considerable improvements in national legislation, health system responses and community level development, IYCF practices in Nigeria are still below expected levels. Strengthening community and facility based participation, and broader stand-alone/integrated IYCF policy implementations are needed to improve the current feeding practices of Nigerian mothers.